2001
DOI: 10.1007/s004390100524
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the melanocortin-1 receptor andP genes contributes to inter-individual variation in skin pigmentation phenotypes in a Tibetan population

Abstract: The melanocortin-1 receptor (MC1R) and P gene product are two important components of the human pigmentary system that have been shown to be associated with red hair/fair skin and cause type II oculocutaneous albinism, respectively. However, their contribution to inter-individual variation at the population level is not well defined. To this end, we genotyped 3 single nucleotide polymorphisms (SNPs) in the MC1R gene (Arg67Gln, Gln163Arg, Val92Met) and 2 SNPs in the P gene (IVS 13-15 and Gly780Gly) in 184 rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
2
48
0
3
Order By: Relevance
“…Numerous studies have negated involvement of this gene in determination of iris colour variation (Branicki et al 2005). Initial data suggest that epistatic interactions between different genes may also play an important role in eventual determination of phenotypic features (Akey et al 2001;Pastorino et al 2004). Pastorino et al (2004) suggested that MC1R variants that are responsible for red hair colour determination may be masked by other genes in populations with darker pigmentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have negated involvement of this gene in determination of iris colour variation (Branicki et al 2005). Initial data suggest that epistatic interactions between different genes may also play an important role in eventual determination of phenotypic features (Akey et al 2001;Pastorino et al 2004). Pastorino et al (2004) suggested that MC1R variants that are responsible for red hair colour determination may be masked by other genes in populations with darker pigmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic mutations in the OCA2 gene are responsible for one of the most common forms of oculocutaneous albinism in humans (Oetting et al 2005). OCA2 was also linked to natural differences in skin colour (Akey et al 2001) and soon became considered as a major gene involved in determination of iris colour Frudakis et al 2003;Duffy et al 2007). The latest studies indicate that a significant amount of variation in eye colour is explained by an interplay between OCA2 and the gene HERC2, which is located in its neighbourhood (Kayser et al 2008;Sturm et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Another more thoroughly studied pigment gene is OCA2 which is a major gene involved in oculocutaneous albinism in human (Oetting et al 1996). Initially, research that was carried out into the link between OCA2 and normal pigment variation revealed an association between the gene and skin pigmentation (Akey et al 2001). A more thorough study on the evolution of pigmentation variation indicated the minor role of the OCA2 gene in light skin evolution in European descent populations (Norton et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An exception is a study on a Tibetan population; the main effects of these two variants were not significant, but an interaction between V92M and a SNP in OCA2 was associated with an increase in lightness (L*) of skin on the inner upper arm. 43 The association of MC1R variants with skin reflectance still remains unclear in most East Asian populations, including the entire Japanese population; however, some researchers have suggested that positive selection has acted on MC1R alleles in East Asian populations. 38 Therefore, we investigated the effect of MC1R variants on skin pigmentation in a large sample of Japanese people by analyzing association between MC1R variants and skin reflectance objectively quantified with a spectrophotometer, as well as freckling.…”
Section: Introductionmentioning
confidence: 99%